Kinase-independent function of checkpoint kinase 1 (Chk1) in the replication of damaged DNA - Speroni, Juliana (2012)
The checkpoint kinases Chk1 and ATR are broadly known for their role in the response to the accumulation of damaged DNA. Because Chk1 activation requires its phosphorylation by ATR, it is expected that ATR or Chk1 down-regulation should cause similar alterations in the signals triggered by DNA lesions. Intriguingly, we found that Chk1, but not ATR, promotes the progression of replication forks after UV irradiation. Strikingly, this role of Chk1 is independent of its kinase-domain and of its partnership with Claspin. Instead, we demonstrate that the ability of Chk1 to promote replication fork progression on damaged DNA templates relies on its recently identified proliferating cell nuclear antigen-interacting motif, which is required for its release from chromatin after DNA damage. Also supporting the importance of Chk1 release, a histone H2B-Chk1 chimera, which is permanently immobilized in chromatin, is unable to promote the replication of damaged DNA. Moreover, inefficient chromatin dissociation of Chk1 impairs the efficient recruitment of the specialized DNA polymerase η (pol η) to replication-associated foci after UV. Given the critical role of pol η during translesion DNA synthesis (TLS), these findings unveil an unforeseen facet of the regulation by Chk1 of DNA replication. This kinase-independent role of Chk1 is exclusively associated to the maintenance of active replication forks after UV irradiation in a manner in which Chk1 release prompts TLS to avoid replication stalling.